Customer Value Analysis at Citra Elektronik Store Medan - Michael; Sutarno (Cattleya Darmaya Fortuna, 2024)
The purpose of this study was to find out how customer value is at Citra Elektronik Stores, Medan. The data sources used in this study were five informants as data sources who were known to have information about what was researched by the author. Five informants were given the same ten questions in the interview and data analysis used data reduction where the interview results which were believed to have no connection with the customer value indicators were deleted by the authors. The results showed that customer value at Citra Elektronik Store was influenced by product quality which was considered positive by customers, while the services and prices provided were too high causing customer value at Citra Elektronik Store, Medan to decline.